Penerapan Rational Emotive Behavior Therapy Dalam Mengatasi Trauma Psikis Yang Mengalami Toxic Relationship (Studi Kasus Inisial “S” di Women Crisis Center Kota Palembang) - Regina Januarti; Kusnadi Kusnadi; Lena Marianti (ScidacPlus, 2023)
This research is motivated by the problem of toxic relationships in counselees that have an impact on psychological illness and experiencing psychological trauma. The counselor seeks to use the Rational Emotive Behavior Therapy (REBT) technique to help counselees identify irrational views to be rational and encourage counselees to change their views in a more encouraging and helpful direction. Yourself to be better. The research title concerns the Application of Rational Emotive Behavior Therapy in overcoming psychological trauma in adolescents experiencing Toxic Relationships at the Women Crisis Center (WCC) in Palembang City. The research aims to discover trauma symptoms in adolescents experiencing toxic relationships at the Women Crisis Center in Palembang City and to analyze the application of Rational Emotive Behavior Therapy techniques in dealing with unhealthy relationships in adolescents. Researchers use qualitative data collection techniques through observation, interviews, and documentation. The results of the study are that first, the symptoms of trauma in adolescents experiencing Toxic relationships at the Women Crisis Center in Palembang City are starting to lose self-confidence, triggering excessive emotions, always lying with their own words, committing violence if they feel unhappy with the actions or attitudes of client S as well as limiting the client's interactions with other people to make the client feel constrained and create a feeling of trauma and fear for the client with what is called a dating relationship. Second, the application of Rational Emotive Behavior Therapy techniques in dealing with Toxic Relationships in adolescents, namely through three stages to obtain the results of handling Toxic relationships in young client S, where the initial stage (awareness) is an increase in the sense of empathy, respect, sincerity (genuineness), the concreteness of the problem, confrontation. Then in the second stage (process) where the client is diagnosed by convincing the client, increasing client S's awareness, to inviting the client to improve the pattern of irrational thinking to rational thinking.